2006
DOI: 10.1292/jvms.68.773
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Effects of Continuous Propofol Infusion in Horses

Abstract: ABSTRACT. We examined the influence of propofol infusion on cardiovascular system at the rate of 0.14, 0.20 and 0.30 mg/kg/min in six adult Thoroughbred horses. The cardiovascular parameters were heart rate (HR), mean arterial pressure (MAP), mean right atrial pressure (MRAP), stroke volume (SV), cardiac output (CO), systemic vascular resistance (SVR), pre-ejection period (PEP) and ejection time (ET). In order to keep the ventilation conditions constantly, intermittent positive pressure ventilation was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 26 publications
5
21
0
Order By: Relevance
“…In this study, during maintenance of anesthesia, stability of PEP, LVET and PEP/LVET was recorded in agreement with Oku et al. (). In awake dogs breathing room air, Sousa et al.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, during maintenance of anesthesia, stability of PEP, LVET and PEP/LVET was recorded in agreement with Oku et al. (). In awake dogs breathing room air, Sousa et al.…”
Section: Discussionsupporting
confidence: 92%
“…In propofol‐anesthetized horses, PEP prolongation and PEP/LVET increases were observed when the CRI was increased (0.14; 0.20 and 0.30 mg kg −1 minute −1 ) (Oku et al. ). In this study, no differences were observed among treatments for PEP because in all treatments, the same CRI was used.…”
Section: Discussionmentioning
confidence: 99%
“…Similar hemodynamic stability was also observed in horses using the same propofol infusion rate where no changes in Q˙t or SVR, and minimal effect on MAP, were reported (Oku et al. ).…”
Section: Discussionsupporting
confidence: 74%
“…Propofol is a suitable drug for PIVA and TIVA techniques because of its ideal pharmacokinetic profile (Oku et al. , ; de Vries et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Arterial blood pressure was lower compared with that of conscious horses [26], but it did not change significantly during anesthesia. The possible causes of the decrease in HR and arterial blood pressure include a cardiovascular depressant effect of medetomidine [26] and propofol [14,23]. Guaifenesin may also have contributed to the decrease in arterial blood pressure, since it is known to cause a significant decrease in arterial blood pressure without significantly changing HR and cardiac output in horses [13].…”
mentioning
confidence: 99%